Exploring Bhutanese Teacherss Perceptions about Extensive Reading - Pem, Kinley (Bhutan Journal of Research and Development, 2024)
The study empirically examined the Bhutanese teachers’ perception of extensive reading. Thirty-four Bhutanese teachers responded to an online questionnaire and rated their level of agreement on extensive reading (ER) characteristics and the benefits of ER. Participants’ questionnaire responses were analyzed quantitatively using descriptive statistics. The results showed that 1) majority of the teacher participants accepted most of the ER characteristics but showed disagreements with a few others that contradicted the widely accepted views of ER. 2) Most of the participants agreed with the ER benefits in the overall development of language proficiencies in terms of reading, writing, speaking, vocabulary, grammar, and motivation, and the majority disagreed with ER benefits of listening proficiency. However, the mixed results of the study indicated teacher participants’ misconception of extensive reading. Therefore, these findings suggest a need for Extensive reading programs and workshops for Bhutanese Teachers to elucidate the misinterpretation of ER.